Wellbeing and Productivity: A Review of the Literature - Amy Isham (2020)
The UK is currently facing two inter-related socio-economic challenges. One is the now well-documented ‘productivity puzzle’; the crisis of persistent low productivity growth across the economy. The other is low levels in the mental and physical health of the working population, in particular. Wellbeing has been considered as a driver of higher levels of productivity and thus a means of solving the productivity puzzle. However, the relationship between productivity growth and wellbeing is complex and involves many moderating or mediating factors.This report reviews the relationships between the different aspects of wellbeing, productivity, and productivity growth. It is the culmination of a desk-based evidence review, survey, and a mapping workshop held with experts from backgrounds including psychology, sociology, economics, and design. The focus is on wellbeing and labour productivity, although resource productivity and multi-factor productivity are also touched upon at relevant points within the report. Key findings and recommendations for further research are summarised below.